“He for She”: The new wave of the cultural revolution - Varun VM (Freedom from Fear, 2020)
A patriarchal society confers the title of “breadwinners” on ‘him’ and bestows them with the responsibility to earn for the family. This confers another title on him as “head of the family” which thematically corresponds to “white man’s burden” as it creates an illusion that only men are capable of earning for the family. Unfortunately, the phrase “the father is the head of the family” is taught already as a lesson in pre-primary school thereby sowing the seeds of inequality in innocent minds. This illusion, born from the patriarchal mindset, laid the foundation for the socio-economic gender inequalities present today and is the root cause of intergenerational inequality faced by women.